Endogenous Longevity and Optimal Tax Progressivity - Burkhard Heer; Stefan Rohrbacher (Center for Economic Studies and Ifo Institute (CESifo), 2020)
We study the impact of endogenous longevity on optimal tax progressivity and inequality in an overlapping generations model with skill heterogeneity. Higher tax progressivity decreases both the longevity gap and net income inequality, but at the expense of lower average lifetime and lower aggregate labor supply and income. We find that the welfare-maximizing income tax is less progressive than in the case of exogenous longevity and that the present US income tax should redistribute less. Our result is robust to the empirically observed range of labor supply elasticity and the assumptions of both missing annuity markets and tax deductibility of private health expenditures.
Keywords: I14; J10; H21; H51; D31; 330; health and inequality; demography; second-best; optimal taxation; personal income distribution; overlapping generations